LONG-TERM OUTCOMES OF CATHETER ABLATION PULMONARY VEINS ON EXAMPLE OF A CLINICAL CASE PATIENT WITH PAROXYSMAL ATRIAL FIBRILLATION - Zolotarova, T. V.; Abu Rabia, S.; Brynza, M. S.; Volkov, D. E. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2017)
Catheter ablation of the pulmonary veins is the method of choice for the treatment of patients with symptomatic paroxysmal atrial fibrillation (AF). However, there are may be complications or recurrence of AF paroxysms and as we have described in our clinical case 2 after ablation really important to conclude that ablation does not eliminate drug therapy, but modifies it.According to recent studies it has been demonstrated that pulmonary vein CA has favourable outcomes at 6–12 months post-ablation, but there are only few studies with a long-term follow-up and, as we see on our clinical case, after 2 years patient present with current deterioration of AF. The vast majority of very longstanding paroxysmal/persistent AF patients maintained sinus rhythm at a mean follow-up time of 5 years following CA, associated with a significant improvement in symptom scores and, as we see on our clinical case, after 2 years patient maintained sinus rhythm, but with recurrence paroxysms of AF for last year with mild/moderate of symptom scores. Often this procedure is not a radical solution of the problem, and most patients (as it also was shown on the example of our clinical case) are require adjunctive therapies including antiarrhythmics, DC cardioversions and re-ablation and upstream therapy (antihypertensive drugs and so on). Also our patient needs correction of the treatment of arterial hypertension and more properly diagnosis (and treatment) of thyroid disorder, and improvement the regulation at all levels - from the daily rhythm of the HR up to relations in the activity of the vagal activity branches, first of all, interventions in the lifestyle and searching for the optimum time drug administration. Of course, consider the presence of multiple syndromes on presented clinical case, we must not forget about the problem of polypharmacy and try to avoid it (many studies in ambulatory care define polypharmacy as a medication count of five or more medications, but it is practically impossible to investigate the biochemical compatibility in vivo of more than 4 drugs).